Editors’ Introduction: Belonging, Recognition, and Negotiated Futures in Asian Social Life - Asep Muhamad Iqbal (Journal of Asian Social Science Research, 2023)
This issue of the Journal of Asian Social Science Research approachescontemporary Asia through the intertwined questions of belonging andrecognition. The five articles gathered here examine Indonesian atheists’search for civic moral ground, educational exclusion among the Hazarapeople in Afghanistan, misogynic culture in South Korea, IndonesianMuslim diaspora in Western countries, and more than five decades ofIndia–Bangladesh relations. Although they differ in subject matter, nationalsetting, and method, they share a common concern with how individuals,communities, and states negotiate dignity, legitimacy, and voice withinunequal social worlds.